Interplay between RNA interference and transposable elements in mammals - Cornec, Alexis; Poirier, Enzo Z. (Frontiers in Immunology, 2023)
RNA interference (RNAi) plays pleiotropic roles in animal cells, from the post-transcriptional control of gene expression via the production of micro-RNAs, to the inhibition of RNA virus infection. We discuss here the role of RNAi in regulating the expression of self RNAs, and 20 particularly transposable elements (TEs), which are genomic sequences capable of influencing gene expression and disrupting genome architecture. Dicer proteins act as the entry point of the RNAi pathway by detecting and degrading RNA of TE origin, ultimately leading to TE silencing. RNAi similarly targets cellular RNAs such as repeats transcribed from centrosomes.Dicer proteins are thus nucleic acid sensors that recognize self RNA in the form of double-25 stranded RNA, and trigger a silencing RNA interference response.